2011
DOI: 10.1242/dev.067330
|View full text |Cite
|
Sign up to set email alerts
|

Joint morphology in the insect leg: evolutionary history inferred from Notch loss-of-function phenotypes in Drosophila

Abstract: Joints permit efficient locomotion, especially among animals with a rigid skeleton. Joint morphologies vary in the body of individual animals, and the shapes of homologous joints often differ across species. The diverse locomotive behaviors of animals are based, in part, on the developmental and evolutionary history of joint morphogenesis. We showed previously that strictly coordinated cell-differentiation and cell-movement events within the epidermis sculpt the interlocking ball-and-socket joints in the adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…During the early stages of pupal development (2–6h APF) cells in the epithelium of the Drosophila leg imaginal disc change shape (Condic et al, 1991; Greenberg and Hatini, 2011; Mirth and Akam, 2002; Tajiri et al, 2011), and rearrange contacts with their neighbors (Taylor and Adler, 2008), to narrow and so elongate and the future appendage (von Kalm et al, 1995). To examine the rearrangements of the epithelium along the apicobasal axis, we labeled nuclei with Dapi and the lateral membrane domain with Fas3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During the early stages of pupal development (2–6h APF) cells in the epithelium of the Drosophila leg imaginal disc change shape (Condic et al, 1991; Greenberg and Hatini, 2011; Mirth and Akam, 2002; Tajiri et al, 2011), and rearrange contacts with their neighbors (Taylor and Adler, 2008), to narrow and so elongate and the future appendage (von Kalm et al, 1995). To examine the rearrangements of the epithelium along the apicobasal axis, we labeled nuclei with Dapi and the lateral membrane domain with Fas3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of arthropods have side-by-side or uniform flexible articulation joints (Tajiri et al 2011), as found in all argasids and ixodids. Of interest is that N.…”
Section: Arthopod Limbsmentioning
confidence: 99%
“…Development of ball and socket joints in the Neoptera has been linked to Notch signalling and consequent cell differentiation and movement (Tajiri et al 2011(Tajiri et al , 2010.…”
Section: Arthopod Limbsmentioning
confidence: 99%
“…In Drosophila , all joint formation is delayed until metamorphosis. Joint morphogenesis has been described in Drosophila (Mirth and Akam 2002 ), and a detailed evolutionary scenario accounting for different joint morphologies has been proposed (Tajiri et al 2011 ). In Drosophila , the gene regulatory networks patterning the primary and tarsal joints are distinct, but share core components ( Fig.…”
Section: Joint Formationmentioning
confidence: 99%